2014
DOI: 10.1371/journal.pone.0095728
|View full text |Cite
|
Sign up to set email alerts
|

The Mucosal Adjuvant Cyclic di-AMP Exerts Immune Stimulatory Effects on Dendritic Cells and Macrophages

Abstract: The cyclic di-nucleotide bis-(3′,5′)-cyclic dimeric adenosine monophosphate (c-di-AMP) is a candidate mucosal adjuvant with proven efficacy in preclinical models. It was shown to promote specific humoral and cellular immune responses following mucosal administration. To date, there is only fragmentary knowledge on the cellular and molecular mode of action of c-di-AMP. Here, we report on the identification of dendritic cells and macrophages as target cells of c-di-AMP. We show that c-di-AMP induces the cell sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 45 publications
2
21
0
1
Order By: Relevance
“…Cyclic di-AMP released from intracellular pathogens is sensed by STING within the host cytosol and induces a type I IFN response (26)(27)(28)(29)(30)(31)(32)(33)(34). A previous report described IFN-␤ production following c-di-AMP treatment in vivo and in human and murine dendritic cells in vitro (46); how- ever, effects of extracellular c-di-AMP on macrophages have not yet been reported. To assess the impact of extracellular c-di-AMP on macrophage activation, murine primary BMDMs were treated with purified c-di-AMP (0.01 to 10 M) for 3 or 6 h, whereupon RNA was isolated and analyzed for cytokine expression.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclic di-AMP released from intracellular pathogens is sensed by STING within the host cytosol and induces a type I IFN response (26)(27)(28)(29)(30)(31)(32)(33)(34). A previous report described IFN-␤ production following c-di-AMP treatment in vivo and in human and murine dendritic cells in vitro (46); how- ever, effects of extracellular c-di-AMP on macrophages have not yet been reported. To assess the impact of extracellular c-di-AMP on macrophage activation, murine primary BMDMs were treated with purified c-di-AMP (0.01 to 10 M) for 3 or 6 h, whereupon RNA was isolated and analyzed for cytokine expression.…”
Section: Resultsmentioning
confidence: 99%
“…The intracellular niche and immunostimulatory activity of Lm have prompted the development of live, attenuated Lm vaccine vectors that retain the ability to enter the cytoplasm (Bruhn et al, 2007). Similarly, the use of cdNs as adjuvants or in immunotherapeutic formulations has shown significant promise in the therapeutic protection against infectious and malignant disease (Skrnjug et al, 2014). Vaccine and immunotherapeutic formulations that contain c-di-AMP and/or 3′3′-cGAMP may elicit RECON-mediated responses that may shape the outcome and interpretation of these pre-clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…CDNs released from bacterial biofilm can also activate host immune responses . Previous studies showed that CDNs could be used as novel vaccine adjuvants or immunostimulatory molecules for host defense . Intranasal administration with c‐di‐GMP enhances bacteria clearance and protects mice from Klebsiella pneumoniae infection through stimulation of dendritic cell‐meditated responses .…”
Section: Introductionmentioning
confidence: 99%